Cooperative Control for Moving-Target Circular Formation of Nonholonomic Vehicles - Yu, Xiao; Liu, Lu (IEEE transactions on automatic control, 2017)
This note investigates the problem of moving-target circular formation of nonholonomic vehicles, such that the controlled vehicles orbit around a target moving with a time-varying velocity and maintain even spacing along the common circle. A cooperative controller is developed for each vehicle via local measurements only. The topology of the sensor graph may dynamically switch based on the relative positions between vehicles and the target. Moreover, measurements in the local Frenet-Serret frame of each vehicle rather than in a global coordinate frame are used. Finally, the effectiveness of the proposed controller is verified by the simulation results of an example.